Redefining the surface anatomy of the saphenofemoral junction in vivo. Issue 6 (20th March 2014) - Ali Mirjalili, S.; Muirhead, Jill C.; Stringer, Mark D.
<x xml:space="preserve">Abstract</x> The surface anatomy of the saphenofemoral junction (SFJ) is especially relevant to surgeons. It is variably described in contemporary anatomy and clinical texts but is usually stated to lie 2.5–4 cm below and lateral to the pubic tubercle. The aim of this study was to map the SFJ accurately in healthy adults using ultrasound. One hundred healthy adults (mean age 27 years; 64 men) were scanned by an experienced sonographer using a 13–5 MHz linear probe. The center of the SFJ was recorded bilaterally in relation to the most superficial point of the pubic tubercle. The SFJ was readily identified in all participants. Its center was a mean of 2.4 ± 0.6 cm lateral (range 1–4.5 cm) and 1 ± 0.9 cm inferior to the pubic tubercle (range 2.5 above to 4 cm caudal to it). The junction was inferior to the pubic tubercle in 90% of lower limbs and at or above that level in 10%. In men, the SFJ was a mean of 2.6 cm lateral to the pubic tubercle and 1.2 cm inferior to it, compared with 2.2 and 0.6 cm, respectively, in women (P < 0.001). The SFJ was also slightly nearer the pubic tubercle in younger and thinner participants (P < 0.01). The center of the SFJ lies in a square extending 1–4 cm lateral and up to 3 cm below the pubic tubercle in >90% of adults. The junction is slightly closer to the pubic tubercle in women. These results provide a more robust guide to the surface anatomy of the normal SFJ. Clin. Anat. 27:915–919, 2014. © 2014 Wiley Periodicals, Inc.